CFD MODELING ON STABILITY OF LIQUID CARBON DIOXIDE IN DEEP OCEAN - TAN, CHIN ZHI (IRC, 2018)
Dispersion type of injection is a type of oceanic carbon dioxide sequestration method proposed in Carbon Capture and Storage (CCS) which dispose liquid carbon dioxide through pipe in Deep Ocean. Stability of injected liquid carbon dioxide has been a concern for all researchers. The objectives of this research are to determine the stability of liquid carbon dioxide in 1km of water depth under various operating parameters. This study is restricted to gas-liquid two phase flow and the injection depth is limited at 1km of sea depth. Since the variation of density and temperature of seawater at 1km of sea depth is minor, constant is assumed during the simulation. The simulation model will be focusing on stability of liquid carbon dioxide in Deep Ocean with three variables which are diameter of injector, pressure and flow rate of liquid carbon dioxide. Background study has been conducted thoroughly before defining the boundary condition, fixed and variable parameter. Simulation of the model using ANSYS Fluent is conducted with mesh independency analysis. Through the simulations results, it can be conclude that injection velocity of carbon dioxide is insignificant to the stability of carbon dioxide in Deep Ocean.